Correlation between the polymorphism of growth hormone gene with the growth performance in Shaoxing ducks - Li Li; Xu Qi; Chen Yang; Huang Xuetao; Li Liumeng; Tao Zhonglian; Chen Guohong (浙江大学学报. 农业与生命科学版)
As excellent germplasm resources in China, Shaoxing duck is famous for its high egg production all over the world. Laying traits, rather than the growth and development traits, are the main breeding criteria in the duck breeding at present. We usually use egg laying traits as the main breeding goal, but ignore the growth and development traits, especially in drake breeding. Defective growth and development may lead to the loss of duck breeding value and the low fertilization rate, which will finally reduce the economic benefit of drakes. Thus, drakes' growth traits must be emphasized in breeding of laying ducks. We must pay more attention to the selection of the drakes' growth traits.This study analyzed the correlation between the polymorphism of growth hormone (GH) gene with the growth performance and slaughter in Shaoxing ducks, which provided some reference material for monitoring the growth and development of Shaoxing ducks breeding.As the candidate genes, GH gene is closely related to the growth and development. The SNP loci of GH were scanned by direct sequencing method. The body size was measured at the age of 12 weeks, and the slaughter indexes were measured at the age of 53 weeks. All ducks were sampled randomly according to the group, and the relevance of Shaoxing duck growth performance and slaughter performance were analyzed. The genomic DNA was extracted by phenol chloroform method from blood. All data were sampled randomly according to the group. According to the published GH gene sequence in GenBank, the primers were designed to amplify the sequences of intron 2, exon 4 and exon 5. The SNP loci of GH were scanned by direct sequencing method, and the sequences were compared by using DNAStar to look for the polymorphic loci. The genotype and allele frequencies were calculated and tested by Hardy-Weinberg balance. The correlation between the genotypes and traits was calculated by using statistical software JMP 4.0 (SAS Institute, 2002) to estimate the least square means of traits.The results showed two loci: GH 2 514 A>G, GH 2 691 C>T. The χ2 test revealed that all loci were in the balance of Hardy-Weinberg (P>0.05). For GH (2 514 A>G & 2 691 C>T), 6-week body mass, 8-week body mass, 12-week keel bone length, 53-week chest width of the individuals with genotype TT were higher than the genotype CT. The breast muscle mass, abdominal fat mass and abdominal fat percentage of individuals with genotype TT were significantly higher than those with genotype CT and CC (P<0.05).It is suggested that GH gene may be the major gene which directly control the abdominal fat and breast muscle related traits, or may be tightly linked with the major genes indirectly.